2017
DOI: 10.1167/iovs.17-21955
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sectoral Structure-Function Relationships in Glaucoma: Vessel Density Versus Thickness in the Peripapillary Retinal Nerve Fiber Layer

Abstract: Peripapillary RNFL VD and thickness have different characteristic sectoral structure-function relationships in glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
48
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 37 publications
8
48
1
3
Order By: Relevance
“…19,20 These studies have shown that the floor effects exhibited by OCT-based RNFL parameters, in which increasing VF losses correspond poorly to detectable changes in the measured RNFL thickness, are largely absent from vascular OCT-A parameters. Spatial correlations have also been demonstrated between defects in the VF and vascular density in the corresponding peripapillary regions, using models defined based on hemispherical regions [21][22][23] or sectors [24][25][26][27] from the Garway-Heath map. 28 However, an evaluation of the focal relationships between VF losses and structural and microvasculature measurements at each VF test point has yet to be reported.…”
mentioning
confidence: 99%
“…19,20 These studies have shown that the floor effects exhibited by OCT-based RNFL parameters, in which increasing VF losses correspond poorly to detectable changes in the measured RNFL thickness, are largely absent from vascular OCT-A parameters. Spatial correlations have also been demonstrated between defects in the VF and vascular density in the corresponding peripapillary regions, using models defined based on hemispherical regions [21][22][23] or sectors [24][25][26][27] from the Garway-Heath map. 28 However, an evaluation of the focal relationships between VF losses and structural and microvasculature measurements at each VF test point has yet to be reported.…”
mentioning
confidence: 99%
“…The sectoral VF CMS was adapted from the structure-function correspondence map suggested by Garway-Heath et al [ 22 ] ( Fig 1 ). Prior studies have investigated the sectoral correlation between peripapillary VD and VF loss using the Garway-Heath map and found strong correlation in the infero-temporal (IT), temporal, infero-nasal and supero-temporal (ST) sectors, similar to the correlation between RNFL thickness and VF loss [ 29 , 30 ]. In our study, sectoral macular vascular microcirculation was significantly correlated with sectoral VF CMS in all sectors except for the inferonasal VF CMS with supero-temporal GCIPL blood flow parameters.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, Sakaguchi and al. [ 25 ] have recently demonstrated that peripapillary RNFL vessel density and thickness had different characteristic sectoral structure-function relationships in glaucoma. An RNFL vessel density measurement must take into account the presence of peripapillary atrophy, hence the importance of precise segmentation of the region of interest such as the one provided by the approach introduced in this article.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of 2D vascular networks have been described in numerous publications [ 2 25 ]. Parameters such as the vascular density in terms of the skeleton of vessels, diameter of vessels, perimeter and tortuosity have been demonstrated to be correlated with lesions.…”
Section: Introductionmentioning
confidence: 99%